Ways of Baloma : rethinking magic and kinship from the Trobriands - Mosko, Mark S., 1948- (Malinowski monographs series., 2017)
"Bronislaw Malinowski's path-breaking research in the Trobriand Islands shaped much of modern anthropology's disciplinary paradigm. Yet many conundrums remain. For example, Malinowski asserted that baloma spirits of the dead were responsible for procreation but had limited influence on their living descendants in magic and other matters, claims largely unchallenged by subsequent field investigators, until now. Based on extended fieldwork at Omarakana village--home of the Tabalu "Paramount Chief"--Mark S. Mosko argues instead that these and virtually all contexts of Indigenous sociality are conceived as sacrificial reciprocities between the mirror worlds that baloma and humans inhabit."--Publisher's description